Mal de Río Cuarto virus (MRCV) genomic segment S3 codes for the major core capsid protein - Distefano, Ana Julia (2009)
Mal de Río Cuarto virus (MRCV) is a newly described species of the genus Fijivirus, family Reoviridae. Compared with other plant-infecting genus of the family, the function and localization of MRCV and other Fijivirus proteins are poorly understood. Through analysis of viral particle purifications, we positively identified five structural proteins of approximately 170, 140, 130, 66, and 62 kDa. The protein encoded by MRCV S3 genomic segment was expressed as a fusion protein in Escherichia coli, purified and used for rabbit immunization. The resulting antiserum reacted with the 140 kDa structural protein and with incomplete virus particles in immunoelectron microscopy assays, suggesting that MRCV S3 codes for the major core capsid protein.